Evaluation of Bone Densitometry in Rheumatoid Arthritis Case Control Study - Kader Media , Shwan (Diyala Journal of Medicine, 2021)
Background: Rheumatoid arthritis is a systemic autoimmune inflammatory disease that causes joint deformity, including erosion of bone, and narrowing of the joint space. Osteoporosis is more prevalent among rheumatoid arthritis patients than in the general population. Objective: To determine changes in the bone mineral density in rheumatoid arthritis patients and to evaluate factors were associated with bone mineral density. Patients and Methods: In this study, 70 cases with rheumatoid arthritis were included and 70 healthy subjects on the other hand as a control group. The data were collected including socio-demographic information of all patients’age, gender, medical histories included systemic diseases, types of biological agents, use of supplements, duration of the disease, smoking, and regular exercise. Bone mineral density was evaluated by using bone densitometry in two areas including Lumber 1 to lumber 4 and neck of the left femur. Statistical analyses were performed by using Statistical Package for Social Sciences (SPSS) version 22; Fisher’s exact test and Chi-square test Student’s t-test of two independent samples was used to comparing two means. A p-value of ≤ 0.05 was considered statistically significant. Results: In the rheumatoid arthritis group according to T-spine scores the prevalence of osteoporosis was 22.9%, osteopenia was 42.9% and normal bone mineral density was 34.4% compared with the control group 4.3%,42.9%,52.9% successively which were statistically significant difference between the two groups (p = 0.003). According to femur neck T-scores in the rheumatoid arthritis group, 17.1% had osteoporosis, 34.3% had osteopenia and 48.6% had normal bone mineral density compared with the control group 2.9%,24.3%,72.9 respectively which were statistically significant difference between the two groups (p = 0.003). lumber spine was the commonest site affected by osteoporosis (16 cases,22.9 %)and the second most common site was the femur neck (12 cases ,6.6%). The cases of 50 years and older were most commonly affected by osteoporosis (p-value = 0.0001). No significant association was detected between bone mineral density (as assessed with spine T-scores and femur T-scores) with gender, duration of the disease, BMI, exercise, supplement, systemic disease, and diabetes. Conclusion: Osteoporosis and osteopenia were considered as common complications in rheumatoid arthritis, the age of the patient also considered as a risk factor for reduced bone mineral density.